First bacteraemic human infection with Escherichia albertii. (November 2015) - Inglis, T.J.J.; Merritt, A.J.; Bzdyl, N.; Lansley, S.; Urosevic, M.N.
Abstract: The facultative anaerobic Gram-negative species Escherichia albertii has been isolated from human faeces in gastrointestinal infection and from a range of wild bird species. Here we report the first case of a febrile infection associated with E. albertii bacteraemia in a 76-year-old woman with gastric dysplasia.